Kesejangan antara Rencana dan Implementasi Rencana Pembangunan Jangka Menengah Daerah (RPJMD) Kabupaten Pasuruan Tahun 2013-2018 - Widiyanti, Jaucha Habibah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
This study aims to analyze the occurrence of gaps in the RPJMD of Pasuruan Regency with the realization, and to identify the underlying causes of why gaps happened. Because although the RPJMD is a reference document for determining the direction of a regional development policy, the RPJMD cannot necessarily be used. The implementation of development programs often not in accordance with the plans set out in the RPJMD document. Based on this situation, the problem that discussed in this study is what are the gaps between the planning and implementation of the Regional Medium-Term Development Plan (RPJMD) and what are the causes of the gap. Indicator of the problem in this study refers to 3 (three) aspects of the gap such as in the consistency of program implementation with planning, integration of budget realization with planning, and consistency of implementation time.